Dynamic Compression Plating Versus Interlocking Nail Procedure for Fracture Shaft of Humerus; A Comparative Study - Zahir Khan, Malik Javed Iqbal, Haziq-Dad Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the efficacy of dynamic compression plating against interlocking nail technique for the treatment of humeral shaft fractures. Study Design: Randomized controlled trial Place & Duration: Department of Orthopedic, Mardan Medical Complex, Mardan for the period of two years from April 2020 to October 2021. Methods: Fifty six patients (18-65 years old) of both sexes were included in the study because they had a humeral shaft fracture. The patients were randomly split into two groups. Both the dynamic compression plating group (n = 28) and the interlocking nail group (n = 28) received treatment. Radiographic examination both before and after surgery were performed. At the 12-day post-operative, complications following the operation were observed. The NEERs criteria were used to analyse the results of the functional assessments. Follow-up was taken at 6 months postoperatively. Results: Mean age of patients was 41.46±10.74 years. 42 (75%) patients were males while 25% were females. Road traffic accident was the most common cause found in 37 (66.07%) patients. Mean union time in DCP and INL group was 11.62±3.05 and 13.54±4.73 weeks. Shoulder stiffness was the commonest complication in both groups. At final follow up, in DCP group 24 (85.71%), 2 (7.14%) and 2 (7.14%) patients had excellent, good and fair outcomes, while in group B (INL) 19 (67.86%), 5 (17.86%) and 4 (14.29%) patients had excellent, good and fair outcomes. No significant difference was found in both groups regarding functional outcomes. Patients satisfaction was high in DCP group as compared to INL. Conclusion: Dynamic compression plating shows better outcomes in term of union time, complications and functional outcomes as compared to interlocking nail Technique. Keywords: Dynamic Compression Plating, Interlocking Nailing, Fracture Shaft of Humerus